"Others Think I am Airy-fairy": Practicing Navayana Buddhism in a Dutch Secular Climate. Issue 2 (2nd July 2016) - Wiering, Jelle
Abstract: This article draws attention to Navayana (Western) Buddhists practicing their religiosity while facing a strongly secularized context. Based on data gathered from fieldwork, this article reveals an interesting paradox concerning the importance of material forms in Navayana Buddhism in the Netherlands. While the body and objects were observed to be crucial for the meditation ritual in Navayana Buddhism, their function was strongly downplayed by most practitioners themselves. I suggest that this contradiction reveals a particular coping mechanism mobilized by practitioners in order to cope with a marginalizing, secular environment. Hence, this article sheds new light on discussions about the characteristics of new forms and expressions of religiosity in secular contexts, and additionally questions the primarily theoretical assumptions regarding the passiveness of a secular environment.